Chromatographic Determination of Total Selenium in Biofortified Allium sp. following Piazselenol Formation and Micro-Solid-Phase Extraction - Bogdan M. Bosca (MDPI AG, 2021)
Herein, a method based on selective piazselenol formation is applied for total selenium determination in biofortified Allium species. Piazselenol is formed by reacting Se(IV) with an aromatic diamine, namely 4-nitro-1,2-phenylenediamine, in acidic medium. Samples were digested in a nitric acid/hydrogen peroxide open system, followed by selenate reduction in hydrochloric acid. Reaction conditions were optimized in terms of pH, temperature, reaction time, and other auxiliary reagents for interference removal, namely, EDTA and hydroxylamine. For the extraction of the selectively formed 4-nitro-piazselenol, micro-solid-phase extraction (μSPE) was applied, and the analysis and detection of the corresponding complex was performed by HPLC coupled with DAD. An external standard calibration curve was developed (R2 = 0.9994) with good sensitivity, and was used to calculate the total selenium content from several Allium plants material, with good intermediate precision (RSD% < 16%). The accuracy of the method was evaluated using both, a comparison with an accepted reference method from our previously published data, as well as three certified reference material with recoveries between 84–126%. The limit of detection was determined to be 0.35 μg/g (in solids) and 1.1 μg/L (in solution), while the limit of quantification was 1.07 μg/g and 3.4 μg/L (in solution). Using the proposed method, selenium content can be quickly and accurately determined in several types of samples. In addition, this study present experimental conditions for overcoming the interferences that might be encountered in selenium determination using piazselenol.